Legal Education and State Regulations for Islamic Boarding Schools: Strengthening Legal Literacy at Pondok Pesantren Al Irsyad Bani Thoha, Panongan, Tangerang Regency - Holiludin; Ahmad Bahrul Hikam (IRDH International Journal of Social Sciences & Humanities, 2025)
This research aims to improve the understanding of Islamic boarding school administrators and students in Tangerang Regency, particularly at the Al Irsyad Bani Thoha Islamic Boarding School in Panongan District, regarding legal education and state regulations governing the existence and governance of Islamic boarding schools in Indonesia. This activity was motivated by the discovery that some Islamic boarding school administrators do not have a comprehensive understanding of applicable legal provisions, resulting in weak formal recognition, limited access to assistance, and less than optimal implementation of child protection within the Islamic boarding school environment. The main legal basis discussed includes Law Number 18 of 2019 concerning Islamic Boarding Schools, Regulation of the Minister of Religious Affairs Number 31 of 2020 concerning Islamic Boarding School Education, and other supporting regulations. The implementation method uses an Asset-Based Community Development (ABCD) approach through socialization, group discussions, and simulations of Islamic boarding school registration administration. Participants in the activity consisted of Islamic boarding school leaders, ustadz, and student representatives. The material covered regulatory mapping, legalization procedures, accreditation mechanisms by the Majelis Masyayikh, and the implementation of child-friendly parenting in accordance with the provisions of the Ministry of Religious Affairs. The results of the activity demonstrated a significant increase in participants' understanding of legal and regulatory aspects, with 85% able to re-explain registration procedures, accreditation, and child protection obligations. Several participants expressed their commitment to immediately follow up on the institution's legalization process. This activity is expected to serve as a model for strengthening legal literacy for other Islamic boarding schools in Tangerang Regency.